Forming-Precision-Driven Structure Design of Hydraulic Press： Methodology and Case Study - 李艳聪 张连洪 何柏岩 陈永亮 张淳 (Transactions of Tianjin University, 2015)
The structure stiffness of presses has great effects on the forming precision of workpieces, especially in near-net or net shape forming. Conventionally the stiffness specification of presses is empirically determined, resulting in poor designs with insufficient or over sufficient stiffness of press structures. In this paper, an approach for the structure design of hydraulic presses is proposed, which is forming-precision-driven and can make presses costeffective by lightweight optimization. The approach consists of five steps：（1）the determination of the press stiffness specification in terms of the forming precision requirement of workpieces;（2）the conceptual design of the press structures according to the stiffness and workspace specifications, and the structure configuration of the press;（3）the prototype design of the press structures by equivalently converting the conceptual design to prototypes;（4）the selection of key structure parameters by sensitivity analysis of the prototype design; and（5）the optimization of the prototype design. The approach is demonstrated and validated through a case study of the structure design of a 100 MN hydraulic press.